2015
DOI: 10.1038/sc.2015.212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise training on fitness and walking-related outcomes in ambulatory individuals with chronic incomplete spinal cord injury

Abstract: Study DesignSingle group, pretest-posttest study.ObjectivesTo determine the effects of a non-task-specific, voluntary, progressive aerobic exercise training (AET) intervention on fitness and walking-related outcomes in ambulatory adults with chronic motor-incomplete SCI.SettingRehabilitation research center.MethodsTen ambulatory individuals (50% female; 57.94 ± 9.33 years old; 11.11 ± 9.66 years post injury) completed voluntary, progressive moderate-to-vigorous intensity AET on a recumbent stepper three days p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 50 publications
2
10
1
Order By: Relevance
“…During graded exercise testing, both peak TM speeds and VO 2 peak increased consistently across participants. The average gains of 2-6 ml/kg/min in VO 2 peak and 0.1-0.3 m/s in peak TM speeds approximate changes observed in participants with chronic stroke or SCI following higher intensity TM training [40][41][42] , and gains in participants with iSCI following lower intensity, recumbent stepping training 43 . While the data suggest some functional benefits of high intensity training, kinematic analyses were utilized to provide some insight into strategies used to increase walking speed.…”
Section: Discussionsupporting
confidence: 54%
“…During graded exercise testing, both peak TM speeds and VO 2 peak increased consistently across participants. The average gains of 2-6 ml/kg/min in VO 2 peak and 0.1-0.3 m/s in peak TM speeds approximate changes observed in participants with chronic stroke or SCI following higher intensity TM training [40][41][42] , and gains in participants with iSCI following lower intensity, recumbent stepping training 43 . While the data suggest some functional benefits of high intensity training, kinematic analyses were utilized to provide some insight into strategies used to increase walking speed.…”
Section: Discussionsupporting
confidence: 54%
“…These morphological changes promote a reduction in the capacity to generate torque and strength, a common problem in people with SCI. [1][2][3] The ability to generate strength is an important prerequisite for an individual to carry out his/her daily living activities (DLA), maintaining his/her function and independence. [4][5][6] There are currently a range of different treatments used in clinical practice to increase strength in people with SCI, such as progressive resistance training (PRT), robotic gait training, cycle ergometer, and neuromuscular electrical stimulation (NMES).…”
mentioning
confidence: 99%
“…Foster,et al found improvements in balance, balance confidence, and functional mobility measured by the TUG in the incomplete SCI population, but were a result of performing backward walking training compared to the PBT performed in this case 35 report. DiPiro,et al also found a similar improvement in aerobic capacity in those with 36 incomplete SCI and Hicks,et al found the same in a meta-analysis of those with complete 20 injuries, but both results were after performing specific, aerobic training.…”
Section: Discussionmentioning
confidence: 54%